Modeling and Analysis of Noise Reduction Method in SPAD-Based LiDAR System - Kai Ma; Tao Yin; Na Tian; Zhe Wang; Tian Zhao; Jian Liu; Nanjian Wu; Liyuan Liu (IEEE Photonics Journal, 2023)
Ambient light interference stands as the primary source of noise encountered by the light detection and ranging (LiDAR) systems based on single-photon avalanche diode (SPAD), which seriously restricts the detection range and accuracy of sensors. Multi-event mode and time-gating method are extensively employed due to their effective suppression ability of the ambient light interference with easily implemented circuit structure. However, the current research on these two operational modes is limited to qualitative description, lacking a comprehensive theoretical analysis. This paper investigates the impact of the multi-event mode and time-gating method on enhancing the imaging capabilities of the sensor, employing a probability distribution perspective. A behavioral model is established, enabling the simulation of the comprehensive functionality of a SPAD-based LiDAR system in either first-hit mode or multi-event mode, including the histogramming, coincident detection, time- gating functions. The model can serve as a substitute for the actual circuit in system function validation and parameter optimization, thereby significantly reducing the design and simulation cycle.